SciELO, Scientific Electronic Library Online, a Database of Open Access Journals - Rogerio Meneghini (Laureate Education Inc, 2013)
This essay discusses SciELO, a scientific journal database operating in 14 countries. It covers over 1000 journals providing open access to full text and table sets of scientometrics data. In Brazil it is responsible for a collection of nearly 300 journals, selected along 15 years as the best Brazilian periodicals in natural and social sciences. Nonetheless, they still are national journal in the sense that over 80% of the articles are published by Brazilian scientists. Important initiatives focused on professionalization and internationalization are considered to bring these journals to a higher level of quality and visibility. DOI: 10.18870/hlrc.v3i3.153